Evaluation of Thermal Effects on Slag Cement Concrete’s Strength Properties (2022)
The physical, chemical, and mechanical characteristics of concrete change with heat-fire. The effect of thermal load on Slag cement concrete output must be measured because of the crucial role of thermal resistance in concrete structure performance and operation. This work examines the thermal resistance of Slag cement concrete. The concrete cubes were produced and cured for 28 days and then subjected to varying temperatures range of 100°C, 150°C, 200°C, 250°C, and 300°C. Hardness and compressive strength were measured at 30, 45, and 60 minutes; the sample results were compared to those of ordinary Portland cement used for the study. The findings of this experiment demonstrate that strength loss was 0.45% at 100 °C, 1.75% at 150 °C, 2.67% at 200°C, 5.98% at 250°C and 12.04 % at 300 °C, the hardness property increased from 100° to 150°C but decreased with higher temperatures. However, average concrete loss at 300 °C exceeds 20 percent of its compressive strength. This means that higher temperatures have adverse effects on concrete strength. From the test, however, it has been noted that there was an insignificant loss of strength of concrete at temperatures below 250°C and however, above 250 °C, a significant loss of concrete strength was observed. The results indicate that slag concrete has a significantly higher thermal resistance potential than traditional concrete and can be used even in industrial applications.